Pengendalian Produksi Pascapanen pada IKM Nozy Juice dengan Metode Six Sigma - Didi Asmadi; Ilyas Ilyas; Elda Nadhilah (Universitas Teuku Umar, 2021)
This study aimed to carry out the process of controlling postharvest products, namely the fruits processed into juice produced by the Small and Medium Enterprises (SMEs) Nozy Juice in Banda Aceh. The problem faced is that an uncontrolled production process can cause product damage, which can cause losses. The research methodology used is the six sigma method, and the type of data used is secondary data, namely production process data, production quantities, and damage data. The results showed a sigma level of 3.38, which means there is still a need for improvement or control of the product because there are still product defects. There are three types of defects in the production process, namely 61% damaged stickers, 31% damaged seals, and 8% dirty. Sticker damage is the most dominant defect caused by human factors, work methods, and the environment. The corrective action suggestions are designing and establishing SOP, recording the entire production process, increasing supervision, establishing a reward/punishment system, training employees, and conducting evaluations. The results of this study are expected to provide technical and practical contributions for business actors to improve and maintain product quality, satisfaction, productivity, and profit.